Alcohol Intake and Risk of Injury - Cremonte, Mariana (2014)
Injuries constitute a leading cause of morbidity and mortality in the world, with intentional injuries and those related to traffic most important, due to their social impact and high prevalence. Although alcohol consumption has been identified as a risk factor for injuries, few studies have assessed risk separately for intentional injuries and unintentional injuries caused by traffic, and by other causes. The objective of this paper was to estimate the risk of injuries after acute alcohol consumption for intentional injuries and unintentional traffic and non-traffic injuries, using, alternatively, two exposure measures: self-reported drinking prior to the event and blood alcohol concentration. A probability sample was collected of 540 patients from the emergency department of a hospital in Argentina. Logistic regressions were performed, with and without adjusting for gender, age and drinking pattern. Higher risks were found when blood alcohol concentration was used as a measure of consumption, compared to self-report. The highest risk estimates were obtained for intentional injuries, followed by unintentional traffic and, lastly, by unintentional non-traffic injuries. After controlling for confounders, risks for intentional and unintentional traffic injuries appeared similar for those above and below the legal limit. Results point to a significant involvement of alcohol in the regional context.